2011
DOI: 10.1016/j.trsl.2011.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-enhanced diet reduces noise-induced damage to the inner ear and hearing loss

Abstract: Oxidative stress has been broadly implicated as a cause of cell death and neural degeneration in multiple disease conditions; however, the evidence for successful intervention with dietary antioxidant manipulations has been mixed. In this study, we investigated the potential for protection of cells in the inner ear using a dietary supplement with multiple antioxidant components, selected for their potential interactive effectiveness. Protection against permanent threshold shift (PTS) was observed in CBA/J mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 118 publications
3
50
0
Order By: Relevance
“…It is possible that increasing the nutrient levels further might improve the degree of protection, as there are data suggesting a doseresponse curve exists for mice exposed to noise insult, with higher dietary nutrient content providing better protection against noise insult (Le Prell et al 2011b). However, in addition to the caspase-dependent apoptotic cell death pathways that are initiated by toxic accumulation of free radicals, there are other caspaseindependent cell death pathways activated by aminoglycosides (for recent review, see Steyger 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that increasing the nutrient levels further might improve the degree of protection, as there are data suggesting a doseresponse curve exists for mice exposed to noise insult, with higher dietary nutrient content providing better protection against noise insult (Le Prell et al 2011b). However, in addition to the caspase-dependent apoptotic cell death pathways that are initiated by toxic accumulation of free radicals, there are other caspaseindependent cell death pathways activated by aminoglycosides (for recent review, see Steyger 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The TD.2040 and TD.08623 diets were identical to the diets described above; however, the dietary treatments were initiated 28 days prior to the start of the gentamicin injections, continued during the 14-day period during which the once-daily gentamicin injections were administered and were maintained throughout the 9-week postgentamicin follow-up window. The 28-day pretreatment duration was selected based on the protection against NIHL in mice that were maintained on an enhanced diet for 28 days prior to noise (Le Prell et al 2011b). …”
Section: Experimental Groupsmentioning
confidence: 99%
“…Mg ++ has been demonstrated to increase inner ear blood fl ow (Scheibe et al 2000 ;Haupt and Scheibe 2002 ), and its effi cacy in attenuating NIHL has been demonstrated (Sendowski 2006 ). The ACEMg treatment was administered to guinea pigs (Le Prell et al 2007 ) and CBA/J mice (Le Prell et al 2011 ) showing reduced permanent threshold shifts after NIHL and also reduced threshold shift after gentamicin ototoxicity (Le Prell et al 2014 ). Studies in humans indicate that regular dietary intake of antioxidants correlates with lower risks of hearing loss (Durga et al 2007 ;Shargorodsky et al 2010 ;Choi et al 2014 ).…”
Section: Mitochondria Oxidative Stress and Age-related Hearing Lossmentioning
confidence: 99%
“…In this model, poor maternal health is a common antecedent of both obesity in the child (and subsequent adult) as well as poorer hearing ability. Obesity is also known to be associated with oxidative stress (Henderson et al 2006;Le Prell et al 2011) and development of chronic inflammation (FernandezSanchez et al 2011). These factors may in turn influence CSF pressure, changing CO2 / pH values that impact along the cochlear aqueduct and have an effect primarily in the high frequency turn of the cochlea, where the aqueduct enters the cochlea.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%